The political economy of MGNREGS spending in Andhra Pradesh - Sheahan, Megan; Liu, Yanyan; Barrett, Christopher B.; Narayanan, Sudha (International Food Policy Research Institute, 2014)
While government spending on pro-poor community asset creation and income-transfers could have compounding positive effects on poverty reduction, it is important to first study trends in the allocation of funds, particularly as they relate to the susceptibility of the program to political clientelism. This paper uses expenditure data at the local level in Andhra Pradesh from India’s National Rural Employment Guarantee Scheme, a rights-based program distributing both public and private goods, to investigate the relationship between voting outcomes and program intensity in the seven years straddling a major election. By focusing on one state where accountability and transparency mechanisms have been employed and implementation efforts have been applauded, the authors do not find evidence of blatant vote buying before the 2009 election but do find that patronage played a small part in fund distribution after the 2009 election. Indeed most variation in expenditures is explained by the observed needs of potential beneficiaries, as the scheme intended.